Schistosomiasis mansoni is asssociated with pyogenic liver abscesses in the state of Minas Gerais, Brazil - Rosângela Teixeira; Francis Jardim Pfeilsticker; Giovanna DC Santa Cecília; Vandack Nobre; Lúcia Porto Fonseca; José Carlos Serufo; Paulo Marcos Zech Coelho; José Roberto Lambertucci (Memorias do Instituto Oswaldo Cruz, 2001)
The association between pyogenic liver abscesses and schistosomiasis has been confirmed by clinical and experimental studies. In this retrospective study of 78 patients with pyogenic liver abscesses the association with schistosomiasis has been investigated. Pyodermitis, a known focus of bacteremia, was observed in 19 patients (24%). Blood eosinophilia was observed in 30 patients (39%). Staphylococcus aureus was cultured from abscesses in 17 out of 38 patients (45%). Forty-one out of 57 patients (53%) had stool examination. Schistosoma mansoni was the main parasite identified. Eggs of S. mansoni were also identified in liver biopsies in 7 out of 19 patients who did the exam. The large number of young patients with liver abscesses described here is different from what has been observed in developed countries. This clinical study provide support for the concept that granulomas of S. mansoni in the liver are foci for colonization with S. aureus, which in presence of staphylococcal bacteremia can form liver abscesses.